Escape fire [videorecording (DVD)] : the fight to rescue American healthcare - Heineman, Matthew; Heineman, Matthew; Froemke, Susan; Froemke, Susan; Berwick, Donald M. (Donald Mark), 1946-; Brownlee, Shannon; Jonas, Wayne B.; Nissen, Steven E.; Weil, Andrew (Lionsgate, 2013)
Examines the U.S. healthcare crisis, citing demands for higher profits by the health care industry as the cause. Individuals tell of their experiences with the healthcare system. Health care professionals and other experts offer their opinions on the situation.